Selection framework for powerplant capacity mix. - Manegdeg, Ferdinand G.
This paper illustrates multiattribute decision analysis in selecting powerplant capacity mix for the National Power Corporation that will meet the power demand of the Philippines by 2005. The objective of this study is to provide a framework for the decision making analysis of the Systems Planning Department of National Power Corporation. The preferences of two managers from the Systems Planning Department were elicited. The preferences and value judgments of the two decision makers on specified levels of production cost (capital cost, operation and maintenance costs, thermal energy needed), fatalities, environmental degradation (radioactive waste, sulfuric dioxide, air particulate, nitrogen dioxide and hydrogen sulfide releases), socio-political acceptability and land use were determined. There were ten (10) powerplant capacity mix alternatives generated. The preference model of decision maker 1 is multiplicative while decision maker 2 is multiplicative with additive submodels. The alternatives that maximizes the use of combined cycle gas turbine and the use of fuel oil were ranked first and second, respectively, by the decision makers.